2018
DOI: 10.14412/2074-2711-2018-2-45-51
|View full text |Cite
|
Sign up to set email alerts
|

The relationship and interaction of menstrual and generative function and depressive disorders in women

Abstract: Тювина Н.А., Воронина Е.О., Балабанова В.В., Гончарова Е.М. России, Москва, Россия 119021, Москва, ул. Россолимо, 11, стр. 9 Цель исследования -изучение отдельных аспектов взаимосвязи и взаимовлияния менструально-генеративной функции и депрес-сивных расстройств у женщин. Кафедра психиатрии и наркологии ФГАОУ ВО «Первый Московский государственный медицинский университет им. И.М. Сеченова (Сеченовский университет)» Минздрава

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In particular, psychological stress is a known risk factor for developing functional hypothalamic amenorrhea and menstrual cycle alterations [ 14 16 ], as well as psychological disorders and personality characteristics [ 17 ]. Several studies have shown that high cortisol levels due to stress are often associated with sleep disturbances, depression [ 18 , 19 ] and menstrual irregularities [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, psychological stress is a known risk factor for developing functional hypothalamic amenorrhea and menstrual cycle alterations [ 14 16 ], as well as psychological disorders and personality characteristics [ 17 ]. Several studies have shown that high cortisol levels due to stress are often associated with sleep disturbances, depression [ 18 , 19 ] and menstrual irregularities [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be caused by a stressful life event, such as grief, which could be also associated to other psychological disorders and personality characteristics [17]. Several studies have shown how high cortisol levels due to stress are often associated with sleep disturbances and depression [18,19]. Also, menstrual irregularities, which are associated with high cortisol levels, have been connected to emotional disorders and depression, with sleep disorders [20,21].…”
Section: Introductionmentioning
confidence: 99%